Шляхи оптимізації лікування хворих із незадовільним прогнозом кінцевого зросту - Большова, О. В.; Самсон, О. Я.; Спринчук, Н. А. (Clinical Endocrinology and Endocrine Surgery, 2012)
The article describes and analyzes the results of numerous clinical studies on the correction of short stature in children with various endocrine disorders, such as precocious puberty, after the removal of produced androgen-adrenal tumors, congenital dysfunction of the adrenal cortex, a spondyloepiphyseal dysplasia, Shereshevsky-Turner syndrome, growth hormone deficiency, idiopathic growth retardation, biologically inactive growth hormone. Presented own data on treatment outcomes in the application of recombinant growth hormone preparations and analogues luteinizing hormone -releasing hormone in children with poor prognosis of growth.